Simultaneous integrated dose reduction intensity-modulated radiotherapy applied to an elective nodal area of limited-stage small-cell lung cancer - LIU, ZHIYAN (Exp Ther Med, 2015)
The purpose of this study was to evaluate the clinical efficacy and toxicity of simultaneous integrated dose reduction intensity-modulated radiotherapy (SIR-IMRT) applied to an elective nodal area of patients with limited-stage small-cell lung cancer (LS-SCLC). Between January 2010 and March 2013, 52 patients with LS-SCLC that was treated with SIR-IMRT were retrospectively analyzed. A radiation dose of 54 Gy was administered in 30 fractions (1.8 Gy/fraction) to the planning target volume (PTV). Simultaneously, 60 Gy was administered in 30 fractions (2 Gy/fraction) to the planning gross tumor volume. Radiation-related toxicities were estimated according to the Common Terminology Criteria for Adverse Events (version 3.0). Overall survival (OS), locoregional recurrence-free survival and progression-free survival were estimated using the Kaplan-Meier method. By the last follow-up, the median follow-up time was 16.5 months, the median OS was 24.0 months, and 21 (40.4%) patients had experienced treatment failure. Of these patients, 5 (9.6%) patients developed in-field recurrence (within the 95% isodose curve of the PTV) and 1 (1.9%) patient developed an out-of-field recurrence (not a distant metastasis). Grade 3 or higher treatment-related pneumonia was observed in 4/52 (7.6%) patients, and grade 3 radiation-related esophagitis was experienced by 2/52 (3.8%) patients. The results of this preliminary study suggest that SIR-IMRT is safe and effective for patients with LS-SCLC and should be further evaluated in a large prospective clinical trial.